Nomina Bertindak Datif Bahasa Jepang - Made Ratna Dian Aryani; Ni Luh Kade Yuliani Giri (Balai Bahasa Provinsi Bali, 2023)
This research is focused on nouns that form the dative structure of Japanese, both syntactically and semantically. The purpose of this study is to categorize verbs that give rise to dative and dative-forming elements and to transcribe the meaning of Japanese dative-forming elements. The method used in this research is descriptive qualitative method. This study uses the syntactic theory of Givon regarding verbs, from Dixon about three argument structures, and from Nitta about dative markers. The results of this study indicate that there are (1) Verbs that can give rise to a dative argument can be (a) a continuous verb (keizoku doshi), there are azukeru verb ‘entrust’, moratta ‘have received’, kaite sashiageta ‘has written’, susumete kureta ‘has suggested’, okutte itadaita ‘has received the shipment’, karita ‘have borrowed’, todoketa ‘has reported’, arukaseta ‘has caused it to walk’, wataraseta ‘has caused it to cross’, yomaseta ‘has led to reading’, dan (b) punctual verbs (shunkan doushi), yaitu verba katteshimatta ‘intentionally bought’, shokai shita ‘has introduced’, kinshi shita ‘has forbidden’, dan kubaru ‘will share ’. (2) two types of nouns, namely concrete nouns and abstract nouns. Only concrete noun types can act on dative arguments in BJ sentence structures. AbtrakPenelitian ini difokuskan pada nomina yang membentuk struktur datif bahasa Jepang, baik secara sintaktis, maupun semantis. Tujuan penelitian ini adalah mengategorikan verba yang memunculkan datif dan unsur pembentuk datif serta mentranskripasikan makna unsur datif bahasa Jepang. Metode yang digunakan dalam penelitian ini adalah metode diskriptif kualitatif. Penelitian ini menggunakan teori sintaksis dari Givon mengenai verba, dan Nitta mengenai pemarkah datif. Hasil penelitian ini menunjukkan bahwa terdapat (1) verba-verba yang dapat memunculkan argumen datif dapat berupa (a) verba kontinuatif (keizoku doshi), yaitu verba azukeru ‘menitipkan’, moratta ‘telah menerima’, kaite sashiageta ‘telah menuliskan’, susumete kureta ‘telah menyarankan’, okutte itadaita ‘telah menerima kiriman’, karita ‘telah meminjam’, todoketa ‘telah melaporkan’, arukaseta ‘telah menyebabkan berjalan’, wataraseta ‘telah menyebabkan menyeberang’, yomaseta ‘ telah menyebabkan membaca’, dan (b) verba pungtual (shunkan doushi), yaitu verba katteshimatta ‘sengaja membelikan’, shokai shita ‘telah memperkenalkan’, kinshi shita ‘telah melarang’, dan kubaru ‘akan membagikan’; (2) dua jenis nomina, yaitu nomina konkret dan nomina abstrak. Hanya jenis nomina konkret yang dapat bertindak pada argumen datif dalam struktur bahasa Jepang.